(untitled) (Mother Language, 2025)
This study examines the impact of content language integrated learning (CLIL) on the academic language development of students with language-based learning disabilities (LBLD) in a bilingual context, focusing on the different dynamics between first language (L1) and second language (L2) proficiency. Using a mixed-methods approach, data were collected from teachers, students, and parents. While teachers express positive views on CLIL, the unexpected trend of students favoring the CLIL language (English) over their mother tongue (Bangla) suggests a proficiency gap. Parental concerns include slow language development, motivational challenges, and instances of translation from L2 to L1. Performance data indicate consistent results but unveil challenges for students with LBLD. The study calls for a balanced approach that combines CLIL principles with the strategic use of the mother tongue and addresses motivational factors, offering educators and policymakers essential insights in the context of bilingual education. Mother Language, 2025; 9(1): 132-168